Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $R$ a ring (not necessarily commutative) prove that $x(y-z)=xy - xz$.

\begin{align*} x(y-z)&=x(y+(-z)) \\ &=xy +x(-z) \\ &=xy+-(xz) \\ &=xy-xz \end{align*}

I think all my steps are valid, but I however don't see why:

  1. $a-b=a+(-b)$
  2. $x(-z)=-(xz)$

How can I show this rigoursly ? I was thinking that 1) may be a definition.

share|cite|improve this question
I know the definition of a ring. @DietrichBurde – 90intuition Oct 15 '13 at 21:42
The first one is a definition. We define $a-b$ as the sum $a+(-b)$. – Stefan Hamcke Oct 15 '13 at 21:42
@DietrichBurde I don't see anywhere defined that $a-b=a+(-b)$ – 90intuition Oct 15 '13 at 21:47
@DietrichBurde I see that answer. And I'm aware of that definition. But doesn't define an binary operation $-:R×R→R: (a,b) ↦ a-b = a + (-b) $ Right ? – 90intuition Oct 15 '13 at 21:51
"Some basic properties of a ring follow immediately from the axioms. The additive identity and the additive inverse are unique." – The Chaz 2.0 Oct 15 '13 at 21:51
  1. $a-b=a+(-b)$ by the definition of subtraction.

  2. $x(-z)+xz={?}$.

share|cite|improve this answer
$x(-z)+xz=x(-z+z)=x⋅0=0$. aaaaah ! thanks – 90intuition Oct 15 '13 at 21:45
@90intuition you mean $=x\cdot0=0$ – dfeuer Oct 15 '13 at 21:47
I edited it now. – 90intuition Oct 15 '13 at 21:53

From Wikipedia:

For each $a$ in $R$ there exists $−a$ in $R$ such that $a + (−a) = (−a) + a = 0$ ($−a$ is the inverse element of $a$)

$$ x(y-z)=x(y+(-z)) $$

Multiplication distributes over addition:

$$\begin{align} x(y+(-z))&=xy+x(-z)\\ &=xy-xz,\qquad\text{ as above.} \end{align}$$

share|cite|improve this answer
That definition doesn't define an binary operation "substraction", right ? Something like: $-:R×R→R: (a,b) ↦ a-b = a + (-b)$ – 90intuition Oct 15 '13 at 21:53

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.